2013
DOI: 10.3389/fendo.2013.00023
|View full text |Cite
|
Sign up to set email alerts
|

NPBWR1 and NPBWR2: Implications in Energy Homeostasis, Pain, and Emotion

Abstract: Neuropeptide B/W receptor-1 (NPBWR1) and NPBWR2 had been known as orphan receptors GPR7 and 8, respectively. Endogenous peptide ligands of these receptors, neuropeptide B (NPB) and neuropeptide W (NPW), were identified in 2002 and 2003 (Fujii et al., 2002; Brezillon et al., 2003; Tanaka et al., 2003). These peptides have been implicated in regulation of feeding behavior, energy homeostasis, neuroendocrine function, and modulating inflammatory pain. In addition, strong and discrete expression of their receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Neuropeptide B (NPB) and neuropeptide W (NPW) are endogenous neuropeptide ligands for NPBWR1 and NPBWR2, which are members of the G protein-coupled receptor (GPCR) family, originally termed GPR7 and GPR8, respectively (Tanaka et al, 2003;Sakurai, 2013). Whereas humans and other primates express both NPBWR1 and NPBWR2, a functional NPBWR2 ortholog has not been demonstrated in rodents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropeptide B (NPB) and neuropeptide W (NPW) are endogenous neuropeptide ligands for NPBWR1 and NPBWR2, which are members of the G protein-coupled receptor (GPCR) family, originally termed GPR7 and GPR8, respectively (Tanaka et al, 2003;Sakurai, 2013). Whereas humans and other primates express both NPBWR1 and NPBWR2, a functional NPBWR2 ortholog has not been demonstrated in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…NPB and NPW are encoded by two separate genes and together with NPBWR1 (and NPBWR2 in primates) constitute a neuropeptide-receptor system (Tanaka et al, 2003;Sakurai, 2013). NPB is a 29-amino acid peptide with a unique brominated N-terminal tryptophan; the physiological function of this bromination remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have isolated neuropeptide B (NPB) and neuropeptide W (NPW) as cognate endogenous ligands for NPBWR1 and NPBWR2 (23)(24)(25)(26). NPB and NPW are encoded by two separate genes and together with NPBWR1 (and NPBWR2 in primates) constitute a neuropeptide receptor system (27). NPB consists of 29…”
mentioning
confidence: 99%
“…Another study demonstrated that NPW23 influences the PVN neurons that synthesize oxytocin, vasopressin, and thyrotropinreleasing hormone (Price et al, 2009). These findings suggest that NPW neurons in the PVN are involved in neuroendocrine and autonomic regulation (Sakurai, 2013). In addition, dense NPW-ir fibers were observed in the pig PVN, ARC, VMH, DMH, SON, and LH.…”
Section: Discussionmentioning
confidence: 95%